Plastics Circular Economy and a Sustainable Future: A Strategic Comparative Analysis for SABIC’s Competitive Advantage (aSSIST Business Review, 2026)
This study aims to conduct a comparative analysis of the environmental recycling technologies and strategies of SABIC, BASF, and LG Chem to derive actionable insights to enhance SABIC’s competitiveness. The main research methodology utilizes Porter’s Five Forces, SWOT, and VRIO frameworks and includes an extensive literature review and case analysis. Global chemical companies’ strategies on plastic circular economy and eco-friendly recycling technologies exhibit several commonalities while leveraging distinct approaches to achieve unique competitiveness. All three companies focus on advancing chemical recycling, mechanical recycling, and bio-based technologies to realize a circular economy. SABIC’s TRUCIRCLE™ program accelerates the transition to a circular economy by converting plastic waste into high-value products. BASF’s ChemCycling™ project transforms mixed waste into new chemical feedstocks through pyrolysis, while LG Chem employs supercritical pyrolysis processes to enhance the circularity of plastic resources. To maintain its competitive edge, SABIC must solidify technological differentiation through continuous R&D investment, expand its sustainable product portfolio, and strengthen global partnerships to offer tailored solutions across diverse industries.
Keywords: Circular Economy; Plastics Recycling; SABIC; ESG; Chemical Recycling; Competitive Strategy